(untitled) (International Congress on Economics, Management and Business Studies, 2026)
It is well known that alongside other dimensions of education, cultural education has always been one of the central themes in human life and spiritual maturation. This is because there is no such thing as a person without culture. Some individuals possess a higher level of culture, while others demonstrate a lower one. In other words, every individual, every family, every community, and even every profession has its own distinct and historically shaped culture. Culture emerges together with a person’s language, consciousness, and thinking even before one becomes literate or formally educated. The formation of consciousness and the emergence of language constitute the first steps of personal culture. Even before acquiring formal education, the human ability to draw, sing, create melodies, and observe customs and rituals indicates the initial formation and development of culture.